Advancing the one health approach through integration of Ayush systems: Opportunities and way forward - Shobhit Kumar; K. Madan Gopal; Annu Choudhary; Athira Soman; Uday Ravi Sekhar Namburi (Journal of Family Medicine and Primary Care)
The Ayush systems in India, specifically Ayurveda, have a large pool of infrastructure, human resources, and unique modalities for disease prevention, wellness, and management. These systems have seen significant growth in recent years, with the budget allocation for the Ayush Ministry increasing fourfold from INR 691 crore to INR 3050 crore over the last seven years. The Ayush systems can contribute significantly to the One Health approach, which addresses the interconnectedness of human, animal, and environmental health. The current commentary explores the areas of work related to the One Health approach, the potential role of the Ayush system in addressing these existing policies that support the integration of Ayush in the One Health approach, and future perspectives on the role of Ayush in One Health. Ayush systems advocate preventive measures, such as daily and seasonal regimens and the use of rejuvenating herbs and drugs, as well as therapeutic interventions for a range of health issues. Ayurveda also addresses environmental, animal, and plant health issues and promotes the creation of a healthy ecosystem between humans, animals, and the environment. In addition, Ayush can play a role in addressing zoonotic diseases, noncommunicable diseases, antimicrobial resistance, food safety and health of the elderly, children, and environment. To fully utilize the potential of Ayush in the One Health approach, these systems should be integrated into the healthcare infrastructure and network. Furthermore, initiation of collaborative projects, focused research, training and sensitization of Ayush human resources, and promotion of Ayush-based lifestyles and practices are some of the critical steps required to be taken.